Reconceptualising home, migratory impulse and disenchantment in Helon Habila’s travellers and Chimamanda Adichie’s americanah (2021)
The problematisation of home in the twenty-first century is relatable to the discourse of migration. Existing studies have conceptualised the notion of home and migration from different socio-political perspectives. This paper, while attempting a contrastive of two salient texts, Helon Habila’s Travellers and Chimamanda Adichie’s Americanah, extends on these studies by re-examining the concept, place and essence of home as well as the migratory impulse as the negative force for fuelling the condition of disenchantment. Habila’s Travellers (2019) is a novel that envisions the motifs of home and migration as a double-barrel gun which aggravates immigrants’ traumatic condition. Adichie’s Americanah (2013) strongly foregrounds the subject matter of home, and migratory impulse, while further projecting double disenchantment as a reality of migration. This study adopts Homi Bhabha’s concept of Unhomely and Edward Said’s Orientalism as pivotal postcolonial tenets, while the literary texts are subjected to critical interpretations, with the view to extending the narrative of migration as a key concept in the twenty-first century.